Relapse of Enterococcus hirae Prosthetic Valve Endocarditis - Talarmin, J. P. (American Society for Microbiology, 2011)
Enterococcus hirae, a Gram-positive bacterium, is a rare isolate in clinical specimens. We report an unusual case of a relapse of prosthetic valve endocarditis due to E. hirae 6 months after the initial episode. Clonal relationship was proven by genomic analysis.